Incidence of liver disease in people with HFE mutations. Issue 3 (1st March 2000) - Willis, G; Wimperis, J Z; Lonsdale, R; Fellows, I W; Watson, M A; Skipper, L M; Jennings, B A
Abstract : BACKGROUND: Most patients with haemochromatosis have mutations of the HFE gene. However, the risk to people with HFE mutations of developing disease manifestations of haemochromatosis is not known. AIMS: To determine the risk of developing cirrhosis and liver cancer in individuals with HFE mutations in a population where few people were being treated for haemochromatosis. METHODS: 215 archive biopsy specimens of liver cancer (n=34) and cirrhosis (n=190) were retrieved from histology archives. Blood samples from 1000 individuals from the normal population were also collected. DNA was extracted from the biopsy specimens and exons 2 and 4 of the HFE gene were amplified using polymerase chain reaction. The products were analysed for the C282Y (845A) and H63D (187G) mutations. RESULTS: Three (8.8%) patients from the liver cancer group were homozygous for the C282Y mutation. Five (2.6%) patients from the cirrhosis group were homozygous for the C282Y mutation. One case fell in both the liver cancer and cirrhosis groups. C282Y homozygosity was thus significantly more frequent in both groups than in the normal population. These 215 cases are representative of a population of about 250 000 over 20 years. During this period we estimate that about 260 births or deaths of C282Y homozygous individuals occurred within this population. CONCLUSIONS: A diagnosis of liver cancer or cirrhosis is rare in the lifetime of individuals from this population who are homozygous for the C282Y mutation (2.5%; upper 95% confidence interval (CI) = 8%). Similarly liver disease is rare among C282Y/H63D compound heterozygotes (1%; upper 95% CI = 3.5%).